Case report: Scleromalacia caused by rheumatoid arthritis combined with high intraocular pressure, first discovered due to ocular trauma - Zhang, Yanyan; Wang, Yanyan; Xu, Ruihao; Wang, Tianyu; Zhang, Yuhao; Mao, Jinghai; Yi, Quanyong (Frontiers in Medicine, 2025)
A 53-year-old man with rheumatoid arthritis was first diagnosed with scleromalacia at the ophthalmology clinic after experiencing ocular trauma. The patient presented with decreased vision and abnormalities were subsequently found in his other eye. An ophthalmologist performed emergency debridement and suturing surgery on the ruptured right eyeball, discovering that the sclera was thinned to only 1/5 to 1/3 of its normal thickness. After the operation, the ophthalmologist examined the patient’s right eye and noted similar bluish scleral changes along with elevated intraocular pressure. In this case, we report a relatively rare instance of scleromalacia combined with ocular hypertension, which was definitively diagnosed following emergency ophthalmic surgery. The patient exhibited extremely thin and bluish sclera in both eyes. This case once again underscores the importance of clinicians paying close attention to the impact of systemic autoimmune diseases on ocular health.